Perbandingan Performa dan Kegunaan Unity dan Godot untuk Pengembangan Game First-Person Shooter - Rashied, Faiz Azizan; Purbolaksono, Mahendra Dwifebri; Utama, Dody Qori (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
The paper presents the results of an investigation aimed at identifying the differences between the game engines Unity and Godot in terms of First-Person Shooter (FPS) development. Although the use of the two is widespread, there is a lack of research comparing their performance when subjected to similar experiments. The current study helps to address this gap by measuring the performance of these engines against six key indicators, namely RAM, CPU, frames per second (fps), installation size, export time, and exported build size. The former two engines were chosen since they are the most popular in the industry. Unity 6 and Godot 4.4.1 were put through a series of tests while running the same FPS test scenes on the same hardware (Intel Core i7-10870H, 16 GB RAM, Windows 10). RAM and CPU consumption were measured using Windows Task Manager and verified with the built-in profiler of the engines after three runs. The rest of the variables were measured directly. On average, Godot performed slightly better in terms of RAM (1,108 ± 60 MB), CPU (9.8 ± 0.4%), and fps (143 versus 36), while the installation size of Unity was found to be approximately 71 times larger (170 MB versus 12.1 GB). In addition, Godot took approximately five seconds to export, which is significantly faster than 130 seconds for Unity. The exported build sizes were similar, amounting to 114 MB and 110 MB for Godot and Unity, respectively. Overall, the findings contribute to a preliminary understanding of which engine may be more beneficial in specific conditions, which may be subject to further verification across multiple devices.